1996
DOI: 10.1063/1.361149
|View full text |Cite
|
Sign up to set email alerts
|

Conversion efficiencies from laser-produced plasmas in the extreme ultraviolet regime

Abstract: The conversion efficiency of spectral emission from laser-irradiated solid targets was investigated for short wavelength source development. The plasma brightness was quantified using absolutely calibrated detectors for 20 materials and spectra were obtained between 50 and 200 Å. Laser parameters such as wavelength, pulse length, intensity, and spot size were systematically varied to establish a comprehensive database for source optimization. Qualitative differences in the underlying dominant emission features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 24 publications
2
60
0
1
Order By: Relevance
“…Theoretical and experimental studies [20,[30][31][32] have shown that the~10−μm wavelength generated by CO 2 lasers is favourable for LPP EUV source over the~1−μm wave− length delivered by solid−state lasers in terms of higher CE and reduced debris production [23,24]. An optimal times− cale for an energy coupling from the laser field to the plasma, dictated by the expansion dynamics, was found to be a few nanoseconds for the Nd:YAG lasers [33] and around ten nanoseconds for the CO 2 lasers [31].…”
Section: Pulse Format Requirements For 135 Nm Lpp Euv Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and experimental studies [20,[30][31][32] have shown that the~10−μm wavelength generated by CO 2 lasers is favourable for LPP EUV source over the~1−μm wave− length delivered by solid−state lasers in terms of higher CE and reduced debris production [23,24]. An optimal times− cale for an energy coupling from the laser field to the plasma, dictated by the expansion dynamics, was found to be a few nanoseconds for the Nd:YAG lasers [33] and around ten nanoseconds for the CO 2 lasers [31].…”
Section: Pulse Format Requirements For 135 Nm Lpp Euv Sourcementioning
confidence: 99%
“…This paper focuses on some aspects of EUV source technology applicable to EUVL, in particular laser−pro− duced−plasma (LPP) source emitting at a 13.5−nm wave− length using Sn as a fuel and driven by a pulsed CO 2 laser. Such choice of fuel and driver was shown to be the most practical option for a number of reasons; highest possible conversion efficiency (CE) in a range of 3-6% (at 2−% bandwidth at 13.5 nm) among the low−environmental−haz− ard candidate materials [20,21]; technical feasibility of EUV collection optics with substantial reflectivities around the 13.5 nm [22]; sufficiently small size of the EUV emitting plasma thanks to the focusability of a driv− ing laser beam; low debris production when combined with a 10.6−micron wavelength provided by a CO 2 laser driver [23][24]; and finally the viability of required multi− −kW laser power output of mentioned CO 2 lasers [25][26] allowing for a power scalability. The LPP source principle is also a promising route to a shorter wavelength range of 6.Xnm using Gd as a fuel and is presently an area of active research efforts [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The EUV output was calculated from the LPP device with planar geometry of the target and compared to published the data for tin target [56]. The arrangement of the experiment is shown schematically in Fig.…”
Section: Final Benchmarkmentioning
confidence: 99%
“…According to the literature, R = 60% at around 10 nm. The conversion efficiency could be 10% at maximum, because the reported conversion efficiency for a Ta target is 0.3% / eV at 13 nm 16 and the ellipsoidal mirror used in the present work is capable of focusing LPSXs in a spectral region 100± 20 eV, at least. Compared to the reported efficiency, the conversion efficiency in the present work might be lower because LPSX generation has not yet been optimized.…”
mentioning
confidence: 99%